2011
DOI: 10.1089/neu.2010.1383
|View full text |Cite
|
Sign up to set email alerts
|

Post-Traumatic Seizures Exacerbate Histopathological Damage after Fluid-Percussion Brain Injury

Abstract: The purpose of this study was to investigate the effects of an induced period of post-traumatic epilepsy (PTE) on the histopathological damage caused by traumatic brain injury (TBI). Male Sprague Dawley rats were given a moderate parasagittal fluid-percussion brain injury (1.9-2.1 atm) or sham surgery. At 2 weeks after surgery, seizures were induced by administration of a GABA A receptor antagonist, pentylenetetrazole (PTZ, 30 mg/kg). Seizures were then assessed over a 1-h period using the Racine clinical rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 65 publications
2
26
0
Order By: Relevance
“…[130][131][132] Importantly, PTE is an important secondary injury mechanism that can aggravate damage or impede endogenous recovery mechanisms. [133][134][135][136][137][138][139] In one experimental study, induced periods of PTE were shown to increase the vulnerability of cortical and subcortical structures after experimental TBI. 135 This study first emphasized the potential for a brief episode of PTE to have a significant impact on the vulnerability of the post-traumatic brain.…”
Section: Post-traumatic Epilepsy and Cortical Spreading Depolarizationsmentioning
confidence: 99%
See 1 more Smart Citation
“…[130][131][132] Importantly, PTE is an important secondary injury mechanism that can aggravate damage or impede endogenous recovery mechanisms. [133][134][135][136][137][138][139] In one experimental study, induced periods of PTE were shown to increase the vulnerability of cortical and subcortical structures after experimental TBI. 135 This study first emphasized the potential for a brief episode of PTE to have a significant impact on the vulnerability of the post-traumatic brain.…”
Section: Post-traumatic Epilepsy and Cortical Spreading Depolarizationsmentioning
confidence: 99%
“…[133][134][135][136][137][138][139] In one experimental study, induced periods of PTE were shown to increase the vulnerability of cortical and subcortical structures after experimental TBI. 135 This study first emphasized the potential for a brief episode of PTE to have a significant impact on the vulnerability of the post-traumatic brain. Because recent clinical data have emphasized the high incidence of PTE and episodes of cortical spreading depolarization in TBI patients, these post-traumatic events require more investigation.…”
Section: Post-traumatic Epilepsy and Cortical Spreading Depolarizationsmentioning
confidence: 99%
“…While true normoxia in room air has an FiO 2 *21%, we elected to maintain ''experimental normoxia'' with a ventilatory mixture of nitrous oxide/oxygen (2:1) to produce an FiO 2 = 33%, which is typically used in rat TBI studies (Bales et al, 2010;Bao et al, 2011;Hall and Lifshitz, 2010). Henceforth in this manuscript ''normoxia'' refers to our ''experimental normoxia,'' with an FiO 2 = 33%.…”
Section: Ventilation and Controlled Hypoxiamentioning
confidence: 99%
“…Posttraumatic epilepsy (PTE) is commonly observed in patients with moderate to severe TBI and promotes secondary injury processes and long-term cognitive deficits (Bao, et al, 2011, Vespa, et al, 2010). In models of epilepsy, evidence for acute increases in neurogenesis, similar to that seen after TBI have been reported (Parent, et al, 1997, Scott, et al, 2000).…”
Section: Discussionmentioning
confidence: 99%